0977 Engagement in Collegiate Sleep Health Education: A Matter of Timing. (12th April 2019) - So, Raymond J; Gibney, Sean F; Czeisler, Mark E; Ziporyn, Pallas Snider; Weaver, Matthew D; Barger, Laura K; Klerman, Elizabeth B; Quan, Stuart F; Czeisler, Charles A
Abstract: Introduction: Sleep deficiency and poor sleep hygiene are common among college students. These modifiable factors contribute to adverse mental health, physical health, and academic performance. Sleep health education has been shown to change behavior, improve sleep quality, and reduce the risk of depression. We sought to compare methods of delivering sleep health education to determine which approach optimizes engagement of the student population. Methods: A 45-minute, interactive, online sleep health education program (Sleep 101) was developed to provide college students with a comprehensive understanding of the ways in which sleep impacts health, mood, performance, and safety. The education also included strategies to optimize sleep during college. We provided the online, interactive sleep health education to three separate student groups using different approaches: 1) a mid-semester voluntary activity encouraged with a monetary incentive [10 for completion of the sleep health education module] (MSV) for upper-class undergraduate students, promoted through in-person solicitations outside campus dining areas, newsletter notices and emailed invitations; 2) a pre-matriculation (PMA) activity with a deadline and implied requirement for first-year undergraduate students; or 3) a mid-semester assigned (MSA) activity with a deadline and implied requirement for upper-class undergraduate students. Students were allowed 2 weeks to complete the online sleep health education after it was assigned by the Dean's office. We compared participation rates for each method using descriptive statistics. Results: The MSV, PMA and MSA methods yielded a 4% (17 of 391), 90% (1, 500 of 1, 688) and 25% (1, 238 of 5, 025) completion rate, respectively. Conclusion: The pre-matriculation assigned method for distribution of an undergraduate sleep health education program resulted in the highest engagement. Colleges should consider including sleep health education as a component of assigned pre-matriculation education, as is common for other student health concerns. Support (If Any): Mary Ann & Stanley Snider via Combined Jewish Philanthropies, NIH R01-GM-105018, K24-HL-105664 (EBK).